Olefin multi-block copolymer / silicone rubber composition and foam formed therefrom
By using a composition of high molecular weight silicone rubber and olefin multi-block copolymer, combined with brominated butyl rubber, the problem of difficult wear resistance and high humidity COF in the prior art is solved, and the excellent mechanical properties of the foam are achieved and high humidity friction coefficient.
Patent Information
- Application Number
- CN202211288138.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2017-12-28
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2037-12-28
AI Technical Summary
The existing polymer compositions are difficult to achieve good wear resistance and high humidity COF at the same time, and lack excellent mechanical properties such as compression permanent deformation, resilience and tensile strength.
A composition of silicone rubber including olefin multiblock copolymer and side chain vinyl group is employed, with a weight average molecular weight of ≥ 200,000 g/mole, and brominated butyl rubber is added to the composition to increase wet COF.
The compositions are achieved to provide excellent wear resistance and high humidity COF in single bottom foam applications while improving mechanical properties such as resilience and tensile strength.
Smart Images

Figure CN115850901B_ABST
Abstract
Description
[0001] This invention application is a divisional application based on a patent application with an application date of December 28, 2017, application number 201780097314.X, and invention name “Olefin multi-block copolymer / silicone rubber composition and foam formed therefrom”. Background Art
[0002] Olefin block copolymer (OBC) can be used to form lightweight midsoles. In order to be used as a single-sole foam, the polymer composition should have good wear resistance and good wet-slip resistance (high wet coefficient of friction (wet COF (coefficient of friction))). Although polydimethylsiloxane can be used to improve wear resistance, the wet COF is usually reduced, resulting in poor wet-slip resistance. Foamable compositions and / or other elastomeric compositions are described in the following references: US6767931, US2011 / 0178195, US2015 / 0166755, US2016 / 0160037, KR1075070B1 (Abstract), US7671106, US6013217, US2012 / 0322905, JP3665446B2 (Abstract), CN105670199A (Abstract), CN103709581B (Abstract). However, there is a need for a new polymer composition that provides good wear resistance and good wet COF. There is a further need for such compositions that have good mechanical properties such as compression set, resilience and tensile strength. The following invention has met these needs. Summary of the invention
[0003] A composition comprising at least the following components:
[0004] A) an olefin multi-block copolymer;
[0005] B) Silicone rubber comprising pendant vinyl groups and optionally terminal vinyl groups.
[0006] The present invention comprises:
[0007] 1. A composition comprising at least the following components:
[0008] A) an olefin multi-block copolymer; and
[0009] B) Silicone rubber comprising pendant vinyl groups and optionally terminal vinyl groups.
[0010] 2. The composition according to item 1, wherein the weight average molecular weight (Mw) of the silicone rubber is ≥ 200,000 g / mol.
[0011] 3. The composition according to item 1 or 2, wherein the silicone rubber comprises one or more structures selected from i) and optionally one or more structures selected from ii):
[0012] i) -O-[Si(R)(CH=CH2)]-[Si(R')(R")]-O-, wherein R, R' and R" are each independently an alkyl group, and further a C1-C6 alkyl group, and wherein R, R' and R" may all be the same alkyl group;
[0013] ii) H2C=CH-[Si(R IV )(R V )]-O-, where R IV and R V are each independently an alkyl group, and further a C1-C6 alkyl group, and wherein R IV and R V The alkyl groups may be the same.
[0014] 4. The composition according to any one of the preceding items, wherein the silicone rubber comprises pendant vinyl groups and terminal vinyl groups.
[0015] 5. The composition of any preceding item, wherein the olefin / α-olefin block copolymer has a density of 0.866 g / cc to 0.887 g / cc.
[0016] 6. The composition according to any of the preceding items, wherein the olefin / α-olefin block copolymer has a melt index (I2) of 0.5 to 5.0 g / 10 min (190° C. and 2.16 kg).
[0017] 7. The composition according to any of the preceding items, wherein the olefin multi-block copolymer is an ethylene / α-olefin multi-block copolymer.
[0018] 8. The composition according to any one of the preceding items, wherein the composition comprises 10 wt% to 30 wt% of component B based on the weight of component A and component B.
[0019] 9. An article comprising at least one component formed from the composition according to any preceding claim.
[0020] 10. The article according to item 9, wherein the article is a foam. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 Schematic depicting the different samples cut from Bun Foam.
[0022] Figure 2 Depicted are SEM images of Comparative Example 2 (far left), Comparative Example 3 (middle), and Inventive Example 1 (far right). DETAILED DESCRIPTION
[0023] OBC / silicone rubber compositions have been found to be useful in single bottom foam applications. It has been found that these compositions provide an excellent crosslinking mechanism during foaming and produce foams with good (low DIN) abrasion resistance without significantly reducing the wet COF. These compositions have also been found to have good mechanical properties, such as compression set, resilience and tensile strength. In addition, when used in injection foaming applications, the addition of silicone rubber can aid in the processability of the composition.
[0024] As discussed above, the present invention provides a composition comprising at least the following components:
[0025] A) an olefin multi-block copolymer;
[0026] B) Silicone rubber comprising pendant vinyl groups and optionally terminal vinyl groups.
[0027] An inventive composition may comprise a combination of two or more embodiments as described herein.
[0028] Individual components of the inventive composition may comprise a combination of two or more embodiments as described herein.
[0029] In one embodiment, or a combination of two or more embodiments described herein, the weight average molecular weight (Mw) of the silicone rubber is ≥ 200,000 g / mol, or ≥ 250,000 g / mol, or ≥ 300,000 g / mol, or ≥ 350,000 g / mol, or ≥ 400,000 g / mol, or ≥ 450,000 g / mol, or ≥ 500,000 g / mol.
[0030] In one embodiment, or a combination of two or more embodiments described herein, the silicone rubber comprises one or more structures selected from the following i), and optionally one or more structures selected from ii):
[0031] i) -O-[Si(R)(CH=CH2)]-[Si(R')(R")]-O-, wherein R, R' and R" are each independently an alkyl group, and more preferably a C1-C6 alkyl group, and wherein R, R' and R" may all be the same alkyl group;
[0032] ii) H2C=CH-[Si(R IV )(R V )]-O-, where R IV and R V are each independently alkyl, and more preferably C1-C6 alkyl, and wherein R IV and R VThe alkyl groups may be the same. Here, structure i) represents an internal group of a silicone rubber polymer molecule, which is bonded to an additional part of the polymer molecule at the respective oxygen terminal group. Structure ii) represents an end group of a silicone rubber polymer molecule, which is bonded to an additional part of the polymer molecule at the oxygen terminal group.
[0033] In one embodiment or a combination of two or more embodiments described herein, the silicone rubber includes pendant vinyl groups and terminal vinyl groups.
[0034] In one embodiment or a combination of two or more embodiments described herein, the silicone rubber comprises a structure selected from iii):
[0035] iii) wherein p is 1 to 20, and q is 2000 to 20000. Here, structure i) shows an example of a side chain vinyl group and a terminal vinyl group. In the above structure iii), the side chain vinyl group may be randomly distributed throughout the polymer chain.
[0036] In one embodiment, or a combination of two or more embodiments described herein, the viscosity of the silicone rubber at 25°C is ≥10 6 cSt.
[0037] In one embodiment or a combination of two or more embodiments described herein, the total vinyl (CH2=CH) content of the silicone rubber is ≥ 0.10 mol % based on the weight of the silicone rubber and as determined by 1H NMR.
[0038] In one embodiment, or a combination of two or more embodiments described herein, the silicone rubber further comprises the following structure iv):
[0039] iv) wherein m is 1 to 20,000, and n is 1 to 20,000; R1, R2, R3, and R4 are each independently an alkyl group, and R1, R2, R3, and R4 may be the same alkyl group.
[0040] The silicone rubber may comprise a combination of two or more than two embodiments as described herein.
[0041] In one embodiment, or a combination of two or more embodiments described herein, the olefin / α-olefin block copolymer has a density of 0.866 g / cc to 0.887 g / cc, or 0.868 g / cc to 0.885 g / cc, or 0.870 g / cc to 0.880 g / cc, or 0.872 g / cc to 0.880 g / cc, or 0.874 g / cc to 0.880 g / cc (1 cc = 1 cm 3 ).
[0042] In one embodiment, or a combination of two or more embodiments described herein, the olefin / α-olefin block copolymer has a melt index (I2) of 0.5 to 5.0 g / 10 min, or 1.0 to 4.0 g / 10 min, or 1.0 to 3.0 g / 10 min, or 1.0 to 2.0 g / 10 min (190° C. and 2.16 kg).
[0043] In one embodiment, the melting temperature (Tm) of the olefin multi-block copolymer is 100°C to 135°C, more preferably 110°C to 130°C, more preferably 115°C to 125°C.
[0044] In one embodiment, the olefin multi-block copolymer is an ethylene / α-olefin multi-block copolymer. In another embodiment, the α-olefin is a C3-C8 α-olefin, and more preferably a C4-C8 α-olefin.
[0045] An olefin multi-block copolymer may comprise a combination of two or more than two embodiments as described herein.
[0046] In one embodiment, or a combination of two or more embodiments described herein, the composition comprises ≥70 wt%, or ≥75 wt%, or ≥80 wt%, or ≥85 wt%, or ≥90 wt% of component A, based on the weight of component A and component B.
[0047] In one embodiment or a combination of two or more embodiments described herein, the composition comprises 10 to 30 wt% or 15 to 20 wt% of component B, based on the weight of component A and component B.
[0048] In one embodiment, or a combination of two or more embodiments described herein, the composition comprises ≥60wt%, or ≥65wt%, or ≥70wt%, or ≥75wt%, or ≥80wt%, ≥85wt%, or ≥90wt% of component A and component B, based on the weight of the composition.
[0049] In one embodiment, or a combination of two or more embodiments described herein, the composition further comprises a filler, for example, an inorganic filler (eg, calcium carbonate, talc, silica).
[0050] In one embodiment or a combination of two or more embodiments described herein, the composition further comprises brominated butyl rubber.
[0051] In one embodiment, or a combination of two or more embodiments described herein, the composition further comprises an ethylene-based polymer. In yet another embodiment, the propylene-based polymer is LDPE.
[0052] In one embodiment or a combination of two or more embodiments described herein, the composition further comprises a crosslinking agent (eg, peroxide or triallyl isocyanurate).
[0053] In one embodiment, or a combination of two or more embodiments described herein, the composition further comprises a blowing agent, such as modified azodicarbonamide, benzenesulfonylhydrazide, dinitrosopentamethylenetetramine, sodium bicarbonate, or ammonium carbonate.
[0054] In one embodiment, or a combination of two or more embodiments described herein, the composition includes one or more blowing agent activators (eg, zinc oxide, zinc stearate).
[0055] In one embodiment, or a combination of two or more embodiments described herein, component A is present in the composition in an amount greater than the amount of component B present in the composition.
[0056] In one embodiment, or a combination of two or more embodiments described herein, the composition has an abrasion DIN value of ≤ 220 mm 3 , or ≤210mm 3 , or ≤200mm 3 In one embodiment, the composition has an abrasion DIN value of ≤190 mm. 3 , or ≤180mm 3 , or ≤170mm 3 , or ≤160mm 3 , or ≤150mm 3 In one embodiment, or a combination of two or more embodiments described herein, the composition has an abrasion DIN value of 120 mm 3 Up to 200mm 3 , or 120mm 3 Up to 180mm 3 , or 120mm 3 Up to 160mm 3 .
[0057] In one embodiment, the wet COF value of the composition is ≥ 0.500, or ≥ 0.510, or ≥ 0.520. In one embodiment, or a combination of two or more embodiments described herein, the wet COF value of the composition is ≥ 0.530, or ≥ 0.540, or ≥ 0.550, or ≥ 0.560, or ≥ 0.570, or ≥ 0.580, or ≥ 0.590, or ≥ 0.600. In one embodiment, or a combination of two or more embodiments described herein, the wet COF value of the composition is 0.500 to 0.610, or 0.520 to 0.610, or 0.530 to 0.610, or 0.540 to 0.610, or 0.550 to 0.610.
[0058] In one embodiment, or a combination of two or more embodiments described herein, the resilience of the composition is ≥66% or ≥68%. In one embodiment, or a combination of two or more embodiments described herein, the resilience of the composition is 65% to 70%.
[0059] In one embodiment, or a combination of two or more embodiments described herein, the tensile strength of the composition is ≥2.50 MPa, or ≥2.60 MPa, or ≥2.70 MPa. In one embodiment, or a combination of two or more embodiments described herein, the tensile strength of the composition is 2.50 MPa to 3.20 MPa, or 2.60 MPa to 3.20 MPa, or 2.70 MPa to 3.20 MPa.
[0060] In one embodiment, or a combination of two or more embodiments described herein, the compression set value of the composition is ≤26%, or ≤24%, or ≤22%. In one embodiment, or a combination of two or more embodiments described herein, the compression set value of the composition is 20% to 26%, or 20% to 24%, or 20% to 22%.
[0061] In one embodiment, or a combination of two or more embodiments described herein, the composition has a resilience > 60%, a DIN < 200 mm 3 And wet COF>0.55.
[0062] In one embodiment, or a combination of two or more embodiments described herein, the composition includes ≤1.00wt%, or ≤0.50wt%, or ≤0.20wt%, or ≤0.10wt%, or ≤0.05wt% of a styrenic block copolymer or terpolymer (e.g., SES, SBS, SEP, etc.), based on the weight of the composition. In one embodiment, or a combination of two or more embodiments described herein, the composition does not include a styrenic block copolymer or terpolymer (e.g., SES, SBS, SEP, etc.).
[0063] In one embodiment, or a combination of two or more embodiments described herein, the composition comprises ≤1.00wt%, or ≤0.50wt%, or ≤0.20wt%, or ≤0.10wt%, or ≤0.05wt% polystyrene based on the weight of the composition. In one embodiment, the composition does not include polystyrene.
[0064] In one embodiment, the composition includes ≤ 50 wt%, or ≤ 40 wt%, or ≤ 30 wt%, or ≤ 20 wt%, or ≤ 10 wt% EVA, based on the weight of the composition.
[0065] In one embodiment, or a combination of two or more than two embodiments described herein, the composition comprises ≤1.00wt%, or ≤0.50wt%, or ≤0.20wt%, or ≤0.10wt%, or ≤0.05wt% EVA, based on the weight of the composition. In one embodiment, the composition does not include EVA.
[0066] In one embodiment, or a combination of two or more embodiments described herein, the composition comprises ≤1.00 wt%, or ≤0.50 wt%, or ≤0.20 wt%, or ≤0.10 wt%, or ≤0.05 wt% polyamide based on the weight of the composition. In one embodiment, the composition does not include polyamide.
[0067] An inventive composition may comprise a combination of two or more embodiments as described herein.
[0068] Also provided is an article comprising at least one component formed from a combination of one or more compositions described herein. In yet another embodiment, the article is a foam, and more preferably a single bottom foam. In one embodiment, the foam has a density of 0.20 to 0.30 g / cc, or 0.22 to 0.28 g / cc, or 0.24 to 0.26 g / cc.
[0069] An article may comprise a combination of two or more embodiments as described herein.
[0070] Olefin multi-block copolymers
[0071] The composition of the present invention comprises an olefin multi-block copolymer or an olefin block copolymer. As used herein, an "olefin block copolymer" (OBC) is a multi-block or segmented copolymer and comprises two or more chemically distinct regions or segments (referred to as "blocks") connected in a linear manner, i.e., a polymer comprising chemically differentiated units that are connected end-to-end with respect to polymerized ethylene functional groups rather than in a side-joined or grafted manner. In certain embodiments, the blocks differ in the following aspects: the amount or type of comonomer incorporated therein, the density, the amount of crystallinity, the crystallite size of the polymer that can be attributed to such a composition, the type or degree of stereoregularity (same row or opposite row), the positional regularity or the positional irregularity, the amount of branching (including long chain branching or hyperbranching), homogeneity or any other chemical or physical property. Due to the unique method of manufacturing copolymers, olefin block copolymers are characterized by a polydispersity index (PDI or MDI). w / M n), block length distribution, and / or block number distribution. More specifically, when produced in a continuous process, the PDI of embodiments of the OBC can be in the range of 1.7 to 8; or 1.7 to 3.5; or 1.7 to 2.5; or 1.8 to 2.5; or 1.8 to 2.1. When produced in a batch or semi-batch process, the PDI of embodiments of the OBC can be in the range of 1.0 to 2.9; or 1.3 to 2.5; or 1.4 to 2.0; or 1.4 to 1.8.
[0072] In one embodiment, OBC is an ethylene / α-olefin multi-block copolymer. Ethylene / α-olefin multi-block copolymers include units derived from ethylene in a majority of mole fractions, the ethylene accounting for at least 50 mol%, or at least 60 mol%, or at least 70 mol%, or at least 80 mol%, wherein the remainder of the multi-block copolymer comprises comonomers. Ethylene / α-olefin multi-block copolymers further include ethylene and copolymerizable α-olefin comonomers in polymerized form, characterized by multiple (i.e., two or more than two) blocks or segments of two or more than two polymerized monomer units that are different in chemical or physical properties (block interpolymers), and are multi-block copolymers. In some embodiments, the multi-block copolymer can be represented by the following formula:
[0073] (AB) n ,
[0074] Wherein n is at least 1, preferably an integer greater than 1, such as 2, 3, 4, 5, 10, 15, 20, 30, 40, 50, 60, 70, 80, 90, 100 or more, "A" represents a hard block or segment; and "B" represents a soft block or segment. A and B are connected in a linear manner, not in a branched or star-shaped manner. "Hard" segments refer to blocks of polymerized units, wherein the amount of ethylene present in some embodiments is greater than 95% by weight, and in other embodiments is greater than 98% by weight. In other words, the comonomer content in the hard segment is less than 5% by weight of the total weight of the hard segment in some embodiments, and in other embodiments, less than 2% by weight of the total weight of the hard segment. In some embodiments, the hard segment includes all or substantially all of ethylene.
[0075] On the other hand, a "soft" segment refers to a block of polymerized units wherein the comonomer content is greater than 5% by weight of the total weight of the soft segment in some embodiments, greater than 8% by weight, greater than 10% by weight, or greater than 15% by weight in various other embodiments. In some embodiments, the comonomer content in the soft segment may be greater than 20% by weight, greater than 25% by weight, greater than 30% by weight, greater than 35% by weight, greater than 40% by weight, greater than 45% by weight, greater than 50% by weight, or greater than 60% by weight in various other embodiments.
[0076] Because the individually distinguishable segments or blocks formed from two or more monomers are linked into a single polymer chain, the polymer cannot be fully fractionated using standard selective extraction techniques. For example, a polymer containing relatively crystalline regions (high density segments) and relatively amorphous regions (low density segments) cannot be selectively extracted or fractionated using different solvents. In one embodiment, the amount of polymer extractable using a dialkyl ether or alkane solvent is less than 10%, or less than 7%, or less than 5%, or less than 2% of the total polymer weight.
[0077] In addition, the PDI of the OBC disclosed herein conforms to a Schulz-Flory distribution rather than a Poisson distribution. The OBC of the present invention is made by a polymerization process described in U.S. Pat. No. 7,858,706 and U.S. Pat. No. 7,608,668, which produces a product having a polydisperse block distribution and a polydisperse block size distribution. This results in the formation of an OBC product with distinguishable physical properties. The theoretical benefits of a polydisperse block distribution have previously been modeled and discussed in Potemkin, Physical Review E (1998) 57 (6), pp. 6902-6912 and Dobrynin, J. Chem. Phvs. (1997) 107 (21), pp. 9234-9238.
[0078] In one embodiment, the olefin block copolymer is an ethylene / α-olefin multi-block copolymer. In another embodiment, the ethylene / α-olefin multi-block copolymer has a density of 0.86 to 0.89 g / cc, more preferably 0.87 to 0.88 g / cc (1 cc = 1 cm 3 ).
[0079] In one embodiment, the ethylene / α-olefin multi-block copolymer is defined as having (A) Mw / Mn of 1.7 to 3.5, at least one melting point Tm in degrees Celsius, and a density d in grams per cubic centimeter, wherein the values of Tm and d correspond to the relationship:
[0080] Tm>-2002.9+4538.5(d)-2422.2(d) 2 .
[0081] In one embodiment, the ethylene / α-olefin multi-block copolymer is defined as having (A) Mw / Mn of 1.7 to 3.5, at least one melting point Tm in degrees Celsius, and a density d in grams per cubic centimeter, wherein the values of Tm and d correspond to the relationship:
[0082] Tm>-2002.9+4538.5(d)-2422.2(d)2 ,
[0083] wherein d is 0.866 g / cc, or 0.87 g / cc to 0.89 g / cc, or 0.91 g / cc, or 0.93 g / cc, and Tm is 113°C, or 115°C, or 117°C, or 118°C to 120°C, or 125°C, or 130°C.
[0084] In one embodiment, the ethylene / α-olefin multi-block copolymer is defined as having (B) Mw / Mn of 1.7 to 3.5, and is characterized by a heat of fusion, ΔH, in J / g, and a differential, ΔT, in degrees Celsius, defined as the temperature difference between the tallest DSC peak and the tallest Crystallization Analysis Fractionation ("CRYSTAF") peak, wherein the values of ΔT and ΔH have the following relationship:
[0085] For ΔH greater than zero and up to 130 J / g, ΔT>-0.1299(ΔH)+62.81,
[0086] For △H greater than 130J / g, △T ≥ 48℃,
[0087] Where at least 5% of the cumulative polymer is used to determine the CRYSTAF peak, and if less than 5% of the polymer has an identifiable CRYSTAF peak, then the CRYSTAF temperature is 30°C.
[0088] In one embodiment, the ethylene / α-olefin multi-block copolymer is defined as having (C) an elastic recovery Re in percent measured using a compression molded ethylene / α-olefin interpolymer film at 300% strain and 1 cycle, and having a density d in grams / cubic centimeter, wherein when the ethylene / α-olefin interpolymer is substantially free of a crosslinked phase, the values of Re and d satisfy the following relationship:
[0089] Re>1481-1629(d).
[0090] In one embodiment, the ethylene / α-olefin multi-block copolymer is defined as having (D) a molecular weight fraction eluting between 40°C and 130°C when fractionated using TREF, characterized in that the fraction has a molar comonomer content at least 5% higher than the molar comonomer content of a comparable random ethylene interpolymer fraction eluting between the same temperatures, wherein the comparable random ethylene interpolymer has the same comonomers and has a melt index, density, and molar comonomer content (based on the whole polymer) within 10% of the melt index, density, and molar comonomer content of the ethylene / α-olefin interpolymer.
[0091] In one embodiment, the ethylene / α-olefin multi-block copolymer is defined as having (E) a storage modulus at 25°C, G'(25°C), and a storage modulus at 100°C, G'(100°C), wherein the ratio of G'(25°C) to G'(100°C) is in the range of about 1:1 to about 9:1.
[0092] In one embodiment, the ethylene / α-olefin multi-block copolymer is defined as having (F) a molecular fraction eluting between 40°C and 130°C when fractionated using TREF, characterized in that the block index of the fraction is at least 0.5 and at most about 1, and the molecular weight distribution Mw / Mn is greater than about 1.3. In another embodiment, the molecular weight distribution Mw / Mn of the ethylene / α-olefin multi-block copolymer is less than or equal to about 3.5.
[0093] In one embodiment, the ethylene / α-olefin multi-block copolymer is defined as having an average block index (G) greater than zero and up to about 1.0, and a molecular weight distribution Mw / Mn greater than about 1.3.
[0094] The ethylene / α-olefin multi-block copolymer may have any combination of the above-mentioned properties (A) to (G).
[0095] Non-limiting examples of suitable comonomers include linear / branched α-olefins having 3 to 30 carbon atoms, such as propylene, 1-butene, 1-pentene, 3-methyl-1-butene, 1-hexene, 4-methyl-1-pentene, 3-methyl-1-pentene, 1-octene, 1-decene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-octadecene, and 1-eicosene; cycloolefins having 3 to 30 or 3 to 20 carbon atoms, such as cyclopentene, cycloheptene, norbornene, 5-methyl-2-norbornene, tetracyclododecene, and 2-methyl-1,4,5,8-dimethyl-1,2,3,4,4a,5,8,8a-octahydronaphthalene; Diolefins and polyolefins, such as butadiene, isoprene, 4-methyl-1,3-pentadiene, 1,3-pentadiene, 1,4-pentadiene, 1,5-hexadiene, 1,4-hexadiene, 1,3-hexadiene, 1,3-octadiene, 1,4-octadiene, 1,5-octadiene, 1,6-octadiene, 1,7-octadiene, ethylidene norbornene, vinyl norbornene, dicyclopentadiene, 7-methyl-1,6-octadiene, 4-ethylidene-8-methyl-1,7-nonadiene, and 5,9-dimethyl-1,4,8-decatriene; and 3-phenylpropylene, 4-phenylpropylene, 1,2-difluoroethylene, tetrafluoroethylene, and 3,3,3-trifluoro-1-propylene.
[0096] In one embodiment, the comonomer in the ethylene / α-olefin multi-block copolymer is selected from propylene, butene, hexene or octene.
[0097] In one embodiment, the ethylene / α-olefin multi-block copolymer does not include styrene.
[0098] In one embodiment, the ethylene / α-olefin multi-block copolymer is an ethylene / octene multi-block copolymer. In another embodiment, the density of the ethylene / octene multi-block copolymer is 0.86 to 0.89 g / cc (1 cc = 1 cm 3 ).
[0099] In one embodiment, the soft segment of the ethylene / octene multi-block copolymer comprises 5 mol%, or 7 mol%, or 9 mol%, or 11 mol%, or 13 mol%, or 15 mol% to 18 mol% or 20 mol% of units derived from octene. The density of the ethylene / octene multi-block copolymer is 0.866 g / cc to 0.887 g / cc. The melt index (MI) of the ethylene / octene multi-block copolymer is 0.5 g / 10 min, or 5.0 g / 10 min, or 10 g / 10 min, or 15 g / 10 min to 20 g / 10 min, or 25 g / 10 min, or 30 g / 10 min.
[0100] In one embodiment, the OBC is an ethylene / octene multi-block copolymer having one, some or all of the following properties: a density of 0.866 g / cc to 0.880 g / cc, a melt index of 0.5 g / 10 min to 10 g / 10 min, and a melting temperature of 100°C to 130°C or 110°C to 125°C.
[0101] Olefin multi-block copolymers are available from The Dow Chemical Company under the trade designation INFUSE Olefin Block Copolymers.
[0102] The olefin block copolymer may comprise a combination of two or more than two embodiments as described herein.The ethylene / α-olefin multi-block copolymer may comprise a combination of two or more than two embodiments as described herein.
[0103] additive
[0104] The composition of the present invention may include one or more additives. The additives include but are not limited to antioxidants, ultraviolet absorbers, antistatic agents, pigments, viscosity modifiers, anti-adhesive agents, mold release agents, fillers, coefficient of friction (COF) modifiers, induction heating particles, odor modifiers / adsorbents, and any combination thereof.
[0105] In one embodiment, the composition includes the following, based on the weight of the composition: 50 to 95 wt% of an olefin multi-block copolymer, 5 to 50 wt% of a silicone rubber, 0 to 10 wt% of a brominated butyl rubber, 0.1-10 wt% of a crosslinking agent, 0.1 to 10 wt% of a blowing agent, 0 to 5 wt% of one or more activators, and 0 to 10 wt% of an inorganic filler.
[0106] Overview of Some Embodiments
[0107] 1) A composition comprising at least the following components:
[0108] A) an olefin multi-block copolymer;
[0109] B) Silicone rubber comprising pendant vinyl groups and optionally terminal vinyl groups.
[0110] 2) The composition of 1, wherein the weight average molecular weight (Mw) of the silicone rubber is ≥200,000 g / mol, or ≥250,000 g / mol, or ≥300,000 g / mol, or ≥350,000 g / mol, or ≥400,000 g / mol, or ≥450,000 g / mol, or ≥500,000 g / mol.
[0111] 3) The composition of 1 or 2, wherein the silicone rubber comprises one or more structures selected from the following i), and optionally one or more structures selected from ii):
[0112] i) -O-[Si(R)(CH=CH2)]-[Si(R')(R")]-O-, wherein R, R' and R" are each independently an alkyl group, and more preferably a C1-C6 alkyl group, and wherein R, R' and R" may all be the same alkyl group;
[0113] ii) H2C=CH-[Si(R IV )(R V )]-O-, where R IV and R V are each independently alkyl, and more preferably C1-C6 alkyl, and wherein R IV and R V The alkyl groups may be the same. Here, structure i) represents an internal group of a silicone rubber polymer molecule, which is bonded to an additional part of the polymer molecule at the respective oxygen terminal group. Structure ii) represents an end group of a silicone rubber polymer molecule, which is bonded to an additional part of the polymer molecule at the oxygen terminal group.
[0114] 4) The composition according to any one of 1 to 3, wherein the silicone rubber comprises a side-chain vinyl group and a terminal vinyl group.
[0115] 5) A composition according to any one of 1 to 4, wherein the silicone rubber comprises a structure selected from iii):
[0116] iii) wherein p is 1 to 20, and q is 2000 to 20000. Here, structure i) shows an example of a side chain vinyl group and a terminal vinyl group. In the above structure iii), the side chain vinyl group may be randomly distributed throughout the polymer chain.
[0117] 6) A composition according to any one of items 1 to 5, wherein the viscosity of the silicone rubber at 25°C is ≥10 6 cSt.
[0118] 7) The composition of any one of 1 to 6, wherein the total vinyl (CH2=CH) content of the silicone rubber is ≥ 0.10 mol %, based on the weight of the silicone rubber and as determined by 1H NMR.
[0119] 8) A composition according to any one of items 1 to 7, wherein the silicone rubber further comprises the following structure iv):
[0120] iv) wherein m is 1 to 20,000, and n is 1 to 20,000; R1, R2, R3, and R4 are each independently an alkyl group, and R1, R2, R3, and R4 may be the same alkyl group.
[0121] 9) A composition as described in any one of 1 to 8, wherein the density of the olefin / α-olefin block copolymer is 0.866 g / cc to 0.887 g / cc, or 0.868 g / cc to 0.885 g / cc, or 0.870 g / cc to 0.880 g / cc, or 0.872 g / cc to 0.880 g / cc, or 0.874 g / cc to 0.880 g / cc (1 cc = 1 cm 3 ).
[0122] 10) A composition as described in any one of items 1 to 9, wherein the melt index (I2) of the olefin / α-olefin block copolymer is 0.5 to 5.0 g / 10 min, or 1.0 to 4.0 g / 10 min, or 1.0 to 3.0 g / 10 min, or 1.0 to 2.0 g / 10 min (190°C and 2.16 kg).
[0123] 11) The composition of any one of 1 to 10, wherein the melting temperature (Tm) of the olefin multi-block copolymer is 100°C to 135°C, more preferably 110°C to 130°C, more preferably 115°C to 125°C
[0124] 12) The composition of any one of 1 to 11, wherein the olefin multi-block copolymer is an ethylene / α-olefin multi-block copolymer. In another embodiment, the α-olefin is a C3-C8 α-olefin, and more preferably a C4-C8 α-olefin.
[0125] 13) A composition according to any one of items 1 to 12, wherein based on the weight of component A and component B, the composition comprises ≥70 wt%, or ≥75 wt%, or ≥80 wt%, or ≥85 wt%, or ≥90 wt% of component A.
[0126] 14) The composition of any one of 1-13, wherein based on the weight of component A and component B, the composition comprises 10 to 30 wt%, or 15 to 20 wt% of component B.
[0127] 15) A composition as described in any one of 1-14, wherein the composition comprises ≥60wt%, or ≥65wt%, or ≥70wt%, or ≥75wt%, or ≥80wt%, ≥85wt% or ≥90wt% of component A and component B, based on the weight of the composition.
[0128] 16) The composition according to any one of 1 to 15, wherein the composition further comprises a filler, for example, an inorganic filler (such as calcium carbonate, talc, silicon dioxide).
[0129] 17) The composition of any one of 1-16, wherein the composition further comprises brominated butyl rubber.
[0130] 18) The composition of any one of 1-17, wherein the composition further comprises an ethylene-based polymer. In another embodiment, the propylene-based polymer is LDPE.
[0131] 19) The composition of any one of 1-18, wherein the composition further comprises a crosslinking agent (eg, peroxide or triallyl isocyanurate).
[0132] 20) The composition of any one of items 1-19, wherein the composition further comprises a foaming agent, such as modified azodicarbonamide, benzenesulfonylhydrazide, dinitrosopentamethylenetetramine, sodium bicarbonate or ammonium carbonate.
[0133] 21) A composition according to any one of 1 to 20, wherein the composition comprises one or more foaming agent activators (eg zinc oxide, zinc stearate).
[0134] 22) The composition of any one of 1 to 21, wherein the amount of component A present in the composition is greater than the amount of component B present in the composition.
[0135] 23) A composition according to any one of 1 to 22, wherein the composition has a wear DIN value of ≤220 mm 3 , or ≤210mm3 , or ≤200mm 3 In one embodiment, the composition has an abrasion DIN value of ≤190 mm. 3 , or ≤180mm 3 , or ≤170mm 3 , or ≤160mm 3 , or ≤150mm 3 .
[0136] 24) A composition according to any one of 1 to 23, wherein the abrasion DIN value of the composition is 120 mm 3 Up to 200mm 3 , or 120mm 3 Up to 180mm 3 , or 120mm 3 Up to 160mm 3 .
[0137] 25) The composition of any one of 1-24, wherein the wet COF value of the composition is ≥ 0.500, or ≥ 0.510, or ≥ 0.520.
[0138] 26) A composition as described in any one of 1-25, wherein the wet COF value of the composition is ≥0.530, or ≥0.540, or ≥0.550, or ≥0.560, or ≥0.570, or ≥0.580, or ≥0.590, or ≥0.600.
[0139] 27) A composition as described in any of 1-26, wherein the wet COF value of the composition is 0.500 to 0.610, or 0.520 to 0.610, or 0.530 to 0.610, or 0.540 to 0.610, or 0.550 to 0.610.
[0140] 28) The composition according to any one of 1 to 27, wherein the resilience of the composition is ≥ 66%, or ≥ 68%.
[0141] 29) The composition according to any one of 1 to 28, wherein the composition has a resilience of 65% to 70%.
[0142] 30) A composition as described in any one of 1-29, wherein the tensile strength of the composition is ≥2.50 MPa, or ≥2.60 MPa, or ≥2.70 MPa.
[0143] 31) The composition of any one of items 1-30, wherein the tensile strength of the composition is 2.50 MPa to 3.20 MPa, or 2.60 MPa to 3.20 MPa, or 2.70 MPa to 3.20 MPa.
[0144] 32) The composition according to any one of items 1 to 31, wherein the compression set value of the composition is ≤26%, or ≤24%, or ≤22%.
[0145] 33) The composition of any one of 1-32, wherein the compression set value of the composition is 20% to 26%, or 20% to 24%, or 20% to 22%.
[0146] 34) A composition according to any one of 1 to 33, wherein the composition has a resilience of >60%, a DIN of <200 mm 3 And wet COF>0.55.
[0147] 35) A composition as described in any one of 1-34, wherein the composition comprises ≤1.00wt%, or ≤0.50wt%, or ≤0.20wt%, or ≤0.10wt%, or ≤0.05wt% of a styrene-based block copolymer or terpolymer (e.g., SES, SBS, SEP, etc.), based on the weight of the composition.
[0148] 36) The composition of any one of 1-35, wherein the composition does not include a styrenic block copolymer or terpolymer (eg, SES, SBS, SEP, etc.).
[0149] 37) A composition as described in any one of 1-36, wherein the composition comprises ≤1.00wt%, or ≤0.50wt%, or ≤0.20wt%, or ≤0.10wt%, or ≤0.05wt% of polystyrene based on the weight of the composition.
[0150] 38) A composition as described in any of 1-37, wherein the composition does not include polystyrene.
[0151] 39) A composition as described in any one of 1-38, wherein the composition comprises ≤50wt%, or ≤40wt%, or ≤30wt%, or ≤20wt%, or ≤10wt% EVA based on the weight of the composition.
[0152] 40) A composition as described in any one of 1-39, wherein the composition comprises ≤1.00wt%, or ≤0.50wt%, or ≤0.20wt%, or ≤0.10wt%, or ≤0.05wt% EVA based on the weight of the composition.
[0153] 41) A composition as described in any one of 1-40, wherein the composition does not include EVA.
[0154] 42) The composition of any one of 1-41, wherein the composition comprises ≤1.00 wt%, or ≤0.50 wt%, or ≤0.20 wt%, or ≤0.10 wt%, or ≤0.05 wt% of polyamide, based on the weight of the composition.
[0155] 43) The composition according to any one of 1 to 42, wherein the composition does not comprise polyamide.
[0156] 44) A composition according to any one of 1 to 43, wherein the silicone rubber is not liquid at room temperature (23°C).
[0157] 45) A composition according to any one of 1 to 44, wherein the silicone rubber is solid at room temperature (23°C).
[0158] 46) An article comprising at least one component formed from the composition of any one of 1-45.
[0159] 47) The article of 46, wherein the article is a foam, and more preferably a single-bottom foam.
[0160] 48) The article of 46, wherein the foam has a density of 0.20 to 0.30 g / cc, or 0.22 to 0.28 g / cc, or 0.24 to 0.26 g / cc.
[0161] definition
[0162] Unless stated to the contrary, implicit from the context, or customary in the art, all parts and percentages are by weight and all test methods are current as of the filing date of this disclosure.
[0163] As used herein, the term "composition" encompasses materials comprising the composition, as well as reaction products and decomposition products formed from the materials of the composition.
[0164] The term "comprising" and its derivatives are not intended to exclude the presence of any additional components, steps or procedures, whether or not disclosed herein. For the avoidance of any doubt, unless stated to the contrary, all compositions claimed herein through the use of the term "comprising" may include any additional additives, adjuvants or compounds, whether polymeric or otherwise. In contrast, the term "consisting essentially of excludes from any subsequent enumeration any other components, steps or procedures other than those that are not essential for operability. The term "consisting of excludes any components, steps or procedures that are not specifically described or listed.
[0165] As used herein, the term "polymer" refers to a polymeric compound prepared by polymerizing monomers of the same or different types. The generic term polymer thus encompasses the term homopolymer (used to refer to polymers prepared from only one type of monomer, with the understanding that trace amounts of impurities can be incorporated into the polymer structure), and the term interpolymer as defined below. Trace amounts of impurities can be incorporated into and / or within the polymer.
[0166] As used herein, the term "interpolymer" refers to polymers prepared by the polymerization of at least two different types of monomers. The generic term interpolymer thus includes copolymers (usually employed to refer to polymers prepared from two different types of monomers), and polymers prepared from more than two different types of monomers.
[0167] As used herein, the term "olefin-based polymer" refers to polymers that comprise, in polymerized form, a majority amount of an olefin monomer, such as ethylene or propylene (based on the weight of the polymer), and optionally may include one or more comonomers.
[0168] As used herein, the term "ethylene-based polymer" refers to a polymer that includes a majority weight percent polymerized ethylene monomer (based on the total weight of the polymer), and optionally may include at least one polymerized comonomer.
[0169] As used herein, the term "ethylene / α-olefin interpolymer" refers to an interpolymer that comprises, in polymerized form, a majority amount of ethylene monomer (based on the weight of the interpolymer), and at least one α-olefin. This term does not include olefin block copolymers.
[0170] As used herein, the term "ethylene / α-olefin copolymer" refers to a copolymer comprising in polymerized form a majority amount of ethylene monomer (based on the weight of the copolymer), and α-olefins as the only two monomer types. This term does not include olefin block copolymers.
[0171] As used herein, the term "propylene-based polymer" refers to a polymer that comprises, in polymerized form, a majority amount of propylene monomer (based on the total weight of the polymer), and optionally may include at least one polymerized comonomer.
[0172] Test methods
[0173] GPC-Silicone Rubber
[0174] The chromatography equipment consists of a Waters 2695 separation module equipped with a vacuum degasser and a Waters 2414 refractive index detector. Separation was performed using a STYRAGEL guard column (30 mm × 4.6 mm) followed by three STYRAGEL HR columns (300 mm × 7.8 mm) (molecular weight separation range of 100 to 4,000,000). Certified grade toluene flowing as an eluent at a rate of 1.0 ml / min was used for analysis, and both the column and the detector were heated to 45°C. The sample (0.5% wt / v) was prepared by weighing about 0.025 g of the pure sample into a 12 mL glass vial and diluting with about 5 mL of toluene. After filtering through a 0.45 μm PTFE filter, the sample solution was transferred to a glass autosampler vial. An injection volume of 100 μL was used, and data was collected for 38 minutes. Waters Empower GPC software was used for data acquisition and analysis. Molecular weight averages were determined relative to a calibration curve (Level 3) created using polystyrene standards covering the molecular weight range of 370-1,270,000 g / mole.
[0175] 1 H NMR-Identification of the total vinyl level of silicone products
[0176] For silicone rubber (e.g., RBB-2008-50 and SRB#1):
[0177] The sample (0.05 g) was dissolved in about 2.75 g CDCl3 in a 10 mm NMR tube at 50°C. The spectrometer was run on a Bruker AVANCE 400 MHz spectrometer equipped with a Bruker Dual DUL high temperature CryoProbe and a sample temperature of 50°C. 1 H NMR. Two experiments were performed to obtain spectra, a control spectrum to quantify total polymer protons, and a double presaturation experiment, which suppresses strong polymer backbone peaks and enables high sensitivity spectra for quantification of unsaturation. The control was performed with ZG pulse, 8 scans, 1.64 s, relaxation delay (D1) 30 s. The modified pulse sequence was 100 scans, DS 4, AQ 1.64 s, presaturation time (D1) 1 s, relaxation delay (D 13 )30s to carry out double presaturation experiment.
[0178] For silicone rubber blends (e.g., SPB#2)
[0179] Test samples were prepared by adding 0.05 g of sample to 2.75 g by weight 50 / 50 o-dichlorobenzene-d4 / perchloroethylene with 0.001 M Cr(AcAc)3 in a 10 mm NMR tube. Spectroscopy was performed on a Bruker AVANCE 400 MHz spectrometer equipped with a Bruker Dual DUL high temperature CryoProbe and a sample temperature of 120°C. 1 H NMR. Two experiments were performed to obtain spectra, a control spectrum to quantify total polymer protons, and a double presaturation experiment, which suppressed the strong polymer backbone peaks and enabled high sensitivity spectra for quantification of end groups. The control was performed with a ZG pulse, 16 scans, 1.64 s, relaxation delay (D1) 14 s. The modified pulse sequence was 200 scans, DS 4, AQ 1.64 s, presaturation time (D1) 1 s, relaxation delay (D 13 )13s to carry out double pre-saturation experiment.
[0180] 29 Si NMR - confirming the presence of side chain vinyl groups
[0181] About 0.85 g of sample was dissolved in about 1.5 g of CDCl3 containing 0.025 M Cr(AcAc)3 as a relaxation agent in a 10 mm NMR tube at 50°C. The spectrometer was run on a Bruker AVANCEIII 400 MHz spectrometer equipped with a Bruker 10 mm PABBO probe and a sample temperature of 50°C. 29 Si NMR. Spectra were performed with a ZGIG pulse sequence, 8000 to 10,000 scans, and a 16 s relaxation delay. The PDMS backbone Si unit reference value was -22 ppm. Si attached to a terminal vinyl group was observed at -4 ppm, while Si with a pendant vinyl group was observed at -36 ppm.
[0182] SEM analysis
[0183] Method of cutting foam samples The samples were carefully cut using a single edge blade to obtain SEM images. The samples were coated twice with a conductive coating to ensure good image quality. The samples were then placed in a Nova 630SEM and observed by an ETD detector at 5KV detector accelerating voltage.
[0184] Foam density
[0185] Each Bun foam sample was weighed to the nearest 0.1 gram and the foam volume was determined by measuring the length, width and thickness to the nearest 0.01 cm. Density was calculated based on weight and volume. Samples cut from the Bun foam were Figure 1 .
[0186] Ball rebound (rebound)
[0187] A 5 / 8" diameter steel ball was dropped from a height of 500 mm onto a Bun foam flat plate which was cut vertically from the Bun foam so that the plate had both an upper and a lower skin. The rebound % was calculated as {["rebound height (mm)" / 500 (mm)]*100}.
[0188] Asker C Hardness
[0189] Hardness is the average of five readings (5 second delay) measured on the sample surface according to ASTM D2240.
[0190] Mechanical properties
[0191] Bun foam skin and foam layer were provided for ASTM D638 (tensile, type 4) and ASTM D624 (tear, type C) mechanical property testing, each with a crosshead speed of 20 inches / minute. The sample thickness was about 3 mm. Split tear strength was measured by using a specimen with dimensions of 6 inches (length) x 1 inch (width) x 0.4 inches (thickness) and a notch depth of 1 to 1.5 inches, and at a test speed of 2 inches / minute.
[0192] DIN abrasion test (drum method):
[0193] The DIN abrasion volume loss (in mm) was measured according to ASTM D5963 under a load of 10 N and during this test using a rotation mode (method B, drum 40 rpm), 40 m abrasion. 3 For each foam formulation, a rectangular flat plate (peeled on one surface, about 10 mm thick) was cut from the Bun foam and die cut into discs, each with the following dimensions: 16 mm in diameter and about 10 mm in thickness. The DIN abrasion volume loss was calculated according to the following formula:
[0194]
[0195] in:
[0196] DIN: in mm 3 is the unit wear loss,
[0197] Δm t : Weight loss of the test sample in mg
[0198] ρ t : mg / mm 3 The density of the test specimen in units of
[0199] Δm s : Weight loss of standard rubber in mg.
[0200] The average value is reported based on three test samples.
[0201] Wet COF
[0202] According to ASTM D1894, the wet COF of 230mm stretching distance is measured at a load of 2.7kg and a stretching speed of 100 mm / min. In this test, frosted glass (flat surface) is used as a substrate, and deionized water is evenly dispersed on the glass surface to form a thin water film. For each foam formulation, a rectangular flat plate (peeled on one surface, about 7mm thick) is cut from the Bun foam, and this flat plate is die-cut into a disc, each of which has the following dimensions: about 12.7mm in diameter and about 7mm in thickness). The disc is fixed on a slide with double-sided tape, exposing the epidermal surface and contacting the glass plane. The maximum force Fm (kgf) during the stretching distance is recorded, and the wet COF is calculated as (Fm) / (2.7kgf), and the average wet COF of three test samples is recorded.
[0203] Density - Polymer Samples
[0204] Polymer samples were prepared according to ASTM D 1928. Measurements were made using ASTM D792 Method B within one hour of sample pressing.
[0205] Melt Index
[0206] The melt index (or I2, I2 or MI) of the ethylene-based polymer or OBC or composition of the present invention is measured according to ASTM D 1238, Condition 190°C / 2.16 kg and is reported in grams eluted per 10 minutes.
[0207] DSC Standard Method
[0208] Use differential scanning calorimetry (DSC) to measure the crystallinity of ethylene-based polymer (PE or OBC) sample and propylene-based polymer (PP) sample. Weigh about five to eight milligrams of sample and place in DSC pan. Press lid on pan to ensure airtight atmosphere. Sample pan is placed in DSC unit, and then ethylene-based polymer sample is heated to a temperature of 180°C (230°C for propylene-based polymer sample) at a rate of about 10 degrees Celsius / minute. Keep sample at this temperature for three minutes. Then cool sample to -60°C (-40°C for propylene-based polymer sample) at a rate of 10 degrees Celsius / minute, and isothermally keep three minutes at this temperature. Then heat sample at a rate of 10 degrees Celsius / minute until fully melted (second heating). By adding the heat of fusion (Hf ) divided by the theoretical heat of fusion of 292 J / g for an ethylene-based polymer sample (165 J / g for a propylene-based polymer sample), and multiplying this amount by 100 (e.g., for an ethylene-based polymer sample, % Crystallinity = (H f / 292 J / g)×100; and for propylene-based polymer samples, % crystallinity=(Hf / 165 J / g)×100).
[0209] Unless otherwise stated, the second heating curve obtained from DSC is as described above (peak T m ) to determine the melting point (T m ). From the first cooling curve (peak T c ) to determine the crystallization temperature (T c ).
[0210] Compression set
[0211] Compression set was measured at 50°C according to ASTM D395. For each foam formulation, a rectangular flat plate (peeled on one surface, about 19.5 mm thick) was cut from Bun foam and die cut into discs (button samples), each with the following dimensions: 29 mm (± 0.5 mm) in diameter and about 19.5 mm (± 0.5 mm) thick. Each button sample was inspected for notches, uneven thickness, and non-uniformity, and selected buttons were tested (without those defects). Two specimens of each sample were subjected to compression set at the specified temperature, and the average result of the two specimens was reported. The button sample was placed in a compression device with two metal plates that could be pressed together and locked in place at 50% of the original height of the button sample. The compression device with the compressed sample was then placed in an oven and equilibrated at the appropriate temperature for a specified time (6 hours at 50°C). In this test, the stress was released at the test temperature, and the thickness of the sample was measured after a 30-minute equilibration period at room temperature. Compression set is a measure of how much a sample recovers after compression and is calculated according to the equation CS = (H0-H2) / (H0-H1); where H0 is the original thickness of the sample, H1 is the thickness of the spacer bar used, and H2 is the final thickness of the sample after the compressive force is removed.
[0212] Expansion ratio
[0213] The expansion ratio of Bun foam is calculated by the following formula:
[0214] ER=L1 / L0
[0215] Where L0 is the length of the mold, and L1 is the length of the Bun foam after stabilization (overnight) at room temperature.
[0216] Some embodiments of the present disclosure will now be described in detail in the following examples.
[0217] experiment
[0218] Material
[0219] INFUSE 9100: olefin block copolymer (ethylene / octene multi-block copolymer), density 0.877 g / cm 3 (ASTM D792), MI 1.0 g / 10 min (ASTM D1238, at 190°C / 2.16 kg), Shore A = 75 (ASTM D2240).
[0220] TAISOX 7360M: Ethylene-vinyl acetate copolymer, density 0.941 g / cm 3 (ASTM D792), MI 2.5 g / 10 min (ASTM D1238 at 190°C / 2.16 kg), Shore A = 86 (ASTM D2240), 21 wt% VA content based on the weight of the copolymer.
[0221] ELVAX 265: Ethylene-vinyl acetate copolymer, density 0.951 g / cm 3 (ASTM D792), MI 3.0 g / 10 min (ASTM D1238 at 190°C / 2.16 kg), Shore A = 83 (ASTM D2240), 28 wt% VA content based on the weight of the copolymer.
[0222] ELVAX 40L-03: Ethylene-vinyl acetate copolymer, density 0.967 g / cm 3 (ASTM D792), MI 3.0 g / 10 min (ASTM D1238 at 190°C / 2.16 kg), Shore A = 65 (ASTM D2240), 40 wt% VA content based on the weight of the copolymer.
[0223] RBB 2008-50: Silicone rubber - satisfies the features of component B of claim 1.
[0224] SRB#1: Silicone rubber base #1; Mw about 100000 g / mol; terminal vinyl groups on PDMS only, 29.7 wt% silica content based on the weight of silicone rubber; 0.3 mol% vinyl content (1H NMR) based on the weight of silicone rubber. Vinyl groups can be identified by 1H NMR. 29 Si NMR was used to confirm the presence of pendant vinyl groups and to quantify the level of pendant vinyl groups.
[0225] SPB#2: Silicone Rubber Blend #2, ultra high molecular weight silicone polymer (silicone rubber) dispersed in low density polyethylene (LDPE); silicone polymer level was 50 wt% based on the weight of the blend.
[0226] BIIR 2030: Bromobutyl rubber; density 0.93g / cm 3 (ASTM D792); 32 MU Mooney at temperature = 125°C; 1.8 wt% bromine content based on the weight of the rubber.
[0227] LUPEROX DC40P: Dicumyl peroxide (DCP) from Arkema having an active peroxide content of about 40 wt%.
[0228] LUPEROX DC40P-SP2: A scorch-resistant DCP from Arkema with an active peroxide content of about 40 wt%.
[0229] AC9000: azodicarbonamide type foaming agent. ZnO: zinc oxide. ZnSt: zinc stearate. ATOMITE: calcium carbonate.
[0230] A. Preparation
[0231] The formulations (compositions) are shown in Table 1.
[0232] Table 1: Formulation
[0233]
[0234] EVA*: EVA 7360M / EVA 265 / EVA 40L-03 (30 / 30 / 40, wt / wt / wt)
[0235] Formulation preparation and sample preparation
[0236] Each formulation listed in Table 1 was prepared by using the same method. Taking the CE-1 formulation as an example, the polymer (here only INFUSE 9100 (914 grams)) was added to a "1.5 liter" BANBURY mixer. Then, after the polymer components had melted (about 5 minutes at 120°C), ZnO, ZnSt and CaCO3 were added. Finally, the blowing agent and peroxide were added and mixed for another 3 to 5 minutes at about 120°C (the temperature did not exceed 130°C), with a total mixing time of 15 minutes to form a mixed formulation.
[0237] The mixed formulation was added to a two-roll mill to form a roll-milled blanket (about 5 mm thick). The blanket was cut into squares. Several squares with a total weight of 420 grams were placed in a preheated Bun foam mold (7 inches x 7 inches x 0.5 inches). Preheating was performed at 120°C (no pressure) for 9 minutes and at 120°C and 10 tons of force for 4 minutes. The preheated samples were transferred to the foaming press and heated at 180°C and 4 tons of force (100 kg / cm 2 The Bun Foam was then cooled overnight and then sliced into thin sheets for testing.
[0238] The Bun foam was trimmed into "6 inch x 6 inch" panels using a vertical band saw. The density, hardness, and resilience of the trimmed flat panels (with skins on both surfaces) were measured. The trimmed flat panels were then cut into the desired thickness (about 3 mm thick) using a laboratory-scale horizontal band saw. Thin slices (some with skins and some without skins) were used to measure tensile strength and tear properties. Typically, the remaining middle foam layer of the trimmed Bun foam is used to measure the shrink resistance of the foam. Other portions of the Bun foam are cut into slices of different thicknesses for specific tests; for example, 7 mm thickness for the wet COF test, 10 mm thickness for the DIN abrasion test, 10 mm thickness for the split tear test, and 19.5 mm thickness for the compression set test.
[0239] B. Results and Discussion
[0240] Table 2 below lists the foam (single bottom) properties of the inventive examples and comparative examples, including expansion ratio, foam density with skin, hardness, mechanical properties, DIN abrasion, and wet COF.
[0241] Table 2 Properties of Comparative and Inventive Examples (with Skin)
[0242]
[0243]
[0244] *Two epidermal surfaces (entire slab). **One epidermal surface or epidermal sample.
[0245] The SEM morphology of Comparative Examples 2 and 3 and Inventive Example 1 at the same magnification is shown below. Figure 2 It was found that the foam formed by Inventive Example 1 (single bottom foam) provided a much smaller pore cell size than the foams formed by Comparative Examples 2 and 3, respectively, and that this much smaller pore cell size provided improved tensile strength.
[0246] For Comparative Example 1 and Comparative Examples 2 and 3, the wear resistance can be improved (reduced) by adding conventional PDMS, while the wet COF is significantly reduced. However, by comparing Inventive Example 1 and Comparative Example 2, we can find that at similar foam hardness and wet COF, the foam formed by Inventive Example 1 provides better (worse) wear resistance than the foam formed by Comparative Example 2. In addition, by comparing Inventive Example 1 and Comparative Example 3, it is found that for similar foam hardness and wear resistance, the foam formed by Inventive Example 1 provides a higher wet COF than the foam formed by Comparative Example 3. Therefore, compared with Comparative Examples 2 and 3, Inventive Example 1 provides a better balance of wear and traction. In addition, higher elasticity and higher tensile strength are obtained in the foam (single bottom foam) formed by the Inventive Example.
[0247] By comparing Inventive Example 1 and Comparative Example 4, it has been found that at similar expansion ratios and foam densities, the foam formed by Inventive Example 1 (single bottom foam) provides better abrasion resistance (lower value), better wet skid resistance (higher wet COF), lower compression set and higher resilience than the foam formed by Comparative Example 4 (EVA / silicone rubber).
[0248] By comparing Inventive Example 1 and Comparative Example 5, it has been found that at similar foam hardness and foam density, the foam formed by Inventive Example 1 (silicone rubber with higher molecular weight) provides higher wet COF value and higher resilience while maintaining better (lower) abrasion resistance.
[0249] By comparing Inventive Example 1 with Comparative Examples 3 and 5, it has been found that high molecular weight and side chain vinyl groups (or high vinyl content) are required in the molecular structure of silicone rubber to obtain higher wet COF values. By comparing Inventive Example 1 with Inventive Example 2, it has been found that brominated butyl rubber (BIIR 2030) can be effectively used to increase the COF of OBC / silicone rubber single bottom foams.
[0250] It has also been found that silicone rubbers with high molecular weight (≥200,000 g / mol) and side chain vinyl (vinyl content ≥0.04 wt%) provide better (lower) wear resistance while providing high wet COF values. In addition, higher resilience and higher tensile strength can be obtained from the compositions of the present invention. Single-bottom foams based on such OBC / silicone rubber compositions provide better (lower) wear resistance, better wet skid resistance (higher COF) and higher resilience than EVA / silicone rubber compositions at similar expansion ratios and foam densities. The incorporation of brominated butyl rubber (BIIR) can effectively increase the wet COF of the OBC / silicone rubber compositions of the present invention.
Claims
1. A foamed article formed from a composition, the composition comprising at least the following components: A) an olefin multi-block copolymer; and B) 10 wt% to 30 wt% of a silicone rubber including pendant vinyl groups and terminal vinyl groups, based on the weight of component A and component B, and the weight average molecular weight (Mw) of the silicone rubber is ≥ 200,000 g / mol, wherein the composition does not include EVA, and wherein the composition includes ≥ 85 wt % of component A and component B, based on the weight of the composition.
2. The foam article according to claim 1, wherein the silicone rubber comprises one or more structures selected from i) and one or more structures selected from ii): i) -O-[Si(R)(CH=CH2)]-[Si(R')(R'')]-O-, wherein R, R' and R'' are each independently an alkyl group, and further a C1-C6 alkyl group, and wherein R, R' and R" may all be the same alkyl group; ii) H2C=CH-[Si(R IV )(R V )]-O-, where R IV and R V are each independently an alkyl group, and further a C1-C6 alkyl group, and wherein R IV and R V The alkyl groups may be the same.
3. The foam article according to any one of claims 1 to 2, wherein the olefin multi-block copolymer is an olefin / α-olefin block copolymer, and the density of the olefin / α-olefin block copolymer is from 0.866 g / cc to 0.887 g / cc.
4. The foam article according to any one of claims 1 to 2, wherein the olefin multi-block copolymer is an olefin / α-olefin block copolymer having a melt index (I2) of 0.5 to 5.0 g / 10 min, measured at 190°C and 2.16 kg. 5 . The foam article according to claim 1 , wherein the olefin multi-block copolymer is an ethylene / α-olefin multi-block copolymer.
Citation Information
Patent Citations
A foaming composition for wear-resistant and non-slip shoe soles and its preparation method
CN103709581B
Thermoplastic rubber foam material FRB and preparation method thereof
CN105670199A
Thermoplastic elastomer composition and laminate using the same
JP3665446B2
Method preparing of the foam using composition using foam composition contain ethylene vinyl acetate resin and sillicone rubber
KR101075070B1
Compositions for abrasion resistant foams and methods for making the same
US20110178195A1